Sensory neuron–specific block of multifaceted sodium channels mitigates neuropathic pain behaviors of osteoarthritis - Seung Min Shin; Brandon Itson-Zoske; Hao Xu; Hongfei Xiang; Fan Fan; Quinn H. Hogan; Hongwei Yu (PAIN Reports)
Objective:. Multiple voltage-gated sodium channels (NaVs) in the peripheral sensory neurons (PSNs) regulate action potentials and their dysfunction contributes to the pain pathogenesis of osteoarthritis (OA). A combined block of multiple NaV subtypes selectively in the PSNs may, therefore, represent an effective analgesic approach in OA painful neuropathy. Methods:. To test this hypothesis, we generated recombinant adeno-associated virus (AAV) encoding a potent NaV inhibitory peptide aptamer, termed NaViPA1, that has a multipronged feature of inhibiting tetrodotoxin-sensitive NaV1.7, 1.6, 1.1, and 1.3, characterized in our recent report. Adeno-associated virus-encoded NaViPA1 was delivered into the ipsilateral lumbar 4/5 dorsal root ganglia of rats 2 weeks after induction of knee monoiodoacetate-OA (MIA-OA) and evoked and spontaneous sensory behaviors were followed in 6 weeks. Results:. Expression of NaViPA1 selective in the PSNs produced significant and comparable mitigations of evoked and spontaneous pain behavior and reversal of weight-bearing asymmetry in both male and female MIA-OA rats. Whole-cell current-clamp recordings showed that AAV-mediated NaViPA1 expression normalized action potential firing of the PSNs from MIA animals, suggesting that NaViPA1 attenuated pain behavior by, at least in part, reversing neuronal hyperexcitability. Conclusion:. Together, these results support that (1) NaVs in peripheral sensory pathways contribute to MIA-OA pain pathogenesis and (2) NaViPA1 is a promising analgesic lead that, combined with AAV-targeted delivery to pathological sensory ganglia, may be a viable peripherally selective PSN-targeting strategy in mitigating chronic MIA-OA pain behaviors.